Effectiveness of Non-Pharmacological Interventions on Sleep Quality in Critically Ill Patients: A Systematic Review - Endang Suryaningsih; Joni Haryanto; Candra Panji Asmoro (GLOBAL HEALTH SCIENCE GROUP, 2026)
Sleep disturbances are a common problem in Intensive Care Unit (ICU) patients, which can increase the risk of delirium, anxiety, and other physiological disorders. Therefore, non-pharmacological approaches are important, as these methods are considered safer and have fewer side effects compared to drug-based therapies. This study aimed to evaluate the effectiveness of non-pharmacological interventions, such as earplugs, eye masks, classical music, counseling, and nursing bundles, on sleep quality in ICU patients. This systematic review analyzed 16 articles published between 2021 and 2025, retrieved from PubMed, Proquest, Sage Journals, Science Direct, and Google Scholar databases. Studies meeting the inclusion criteria included randomized controlled trials (RCTs), quasi-experimental designs, or nursing interventions that used instruments to measure sleep quality such as the RCSQ, VSH, and PSQI. 984 articles were obtained and 16 articles were used. Data analysis was conducted narratively using a thematic synthesis approach. All analyzed studies demonstrated a significant improvement in ICU patients' sleep quality after the interventions. The combination of earplugs and eye masks resulted in an average increase in sleep scores of approximately 25–40 points (p<0.001). Furthermore, the implementation of a nursing bundle successfully reduced the incidence of delirium by 15–28%, while the use of classical music and counseling was shown to reduce anxiety levels and improve patient vital signs. The environmental factors most likely to contribute to sleep disturbances were noise (71%), lighting (60%), and nursing procedures performed at night (49%). Non-pharmacological interventions have been shown to be effective in improving sleep quality and reducing the incidence of delirium and anxiety in ICU patients. Therefore, the routine implementation of the combination of earplugs and eye masks, along with an environmentally-based nursing bundle, is highly recommended as part of standard nursing practice in the Intensive Care Unit (ICU).